2022
DOI: 10.1002/aff2.58
|View full text |Cite
|
Sign up to set email alerts
|

Nile tilapia (Oreochromis niloticus Linnaeus, 1758) culture in Kenya: Emerging production technologies and socio‐economic impacts on local livelihoods

Abstract: Nile tilapia (Oreochromis niloticus) is one of the most farmed fish globally, with a significant contribution improving local livelihoods, especially in developing countries. Nile tilapia was first cultured in Kenya in 1924 and is the most cultured fish species. Annually, O. niloticus accounts for 62% (∼15,000 tonnes) of total aquaculture production. Although O. niloticus is the most preferred cultured fish, its culture faces challenges, for example, early maturation due to prolific breeding behaviour leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…Nile tilapia (Oreochromis niloticus) is a widely introduced and cultured fish worldwide. It has become one of the most important fish, with a global harvest of over 6 million tons (MT) [1,2]. Although this fish originated from Africa, the number of countries that farm and culture this fish has increased.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nile tilapia (Oreochromis niloticus) is a widely introduced and cultured fish worldwide. It has become one of the most important fish, with a global harvest of over 6 million tons (MT) [1,2]. Although this fish originated from Africa, the number of countries that farm and culture this fish has increased.…”
Section: Introductionmentioning
confidence: 99%
“…Although this fish originated from Africa, the number of countries that farm and culture this fish has increased. In 2009 reported that 80 countries had farmed tilapia, and it has expanded to over 140 countries ever since, including Indonesia [1,3]. In Indonesia, the freshwater and marine aquaculture industry is crucial to the country's economy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Kenya, aquaculture is the fastest growing subsector due to increased demand for fish and fish products. With the surging demand for locally farmed fish, innovative technologies have emerged to boost aquaculture production (Munguti et al., 2022). Increased aquaculture production should positively correlate with the production of quality feeds to meet the nutritional requirements of cultured fish (Agbo, 2008; Machena & Moehl, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Nile tilapia is the most cultured species in Kenya, accounting for 80% of national aquaculture production but faces challenges of access to quality feeds (Munguti et al., 2022). Few studies have been performed with Nile tilapia to evaluate the effect of crude papain enzyme on growth performance.…”
Section: Introductionmentioning
confidence: 99%